Callus Induction and Plant Regeneration of Brachiaria Grass from Immature Inflorescence Explants - Nilo Suseno; Nofi Isnaini; Bambang Suwignyo; Bambang Suhartanto; Nafiatul Umami (Buletin Peternakan, 2021)
This research was aimed to optimize concentration of phytohormone in callus induction and in vitro regeneration of three species of Brachiaria grass plant, namely Brachiaria brizantha, B. decumbens, and B. ruziziensis. Immature inflorescences were used as explant material. To induce callus, explants were inoculated into Murashige and Skoog (MS) basal medium supplemented with phytohormone combination of 2,4-dichlorophenoxyacetic acid (2,4-D), dicamba and kinetin. Observation of callus induction included percentage of callus formation and callus morphology. The embryogenic calli were then transferred into regeneration media, i.e. MS basal medium supplemented with kinetin and 6-benzylaminopurin (BAP). The result showed that 4 mg/L 2,4-D + 0.2 mg/L kinetin showed highest callus induction in B. brizantha and B. decumbens, namely  76%  and 88% respectively. Whereas in B. ruziziensis, 3 mg/L 2,4-D + 0.2 mg/L kinetin showed highest callus induction, namely 86%. MS medium supplemented with 4 mg/L kinetin showed highest regeneration in all three grass species, namely 92.5% in both B. brizantha and B. ruziziensis, and 88.75% in B. decumbens.